Establishment of porcine embryonic stem-like cells from parthenogenetic and in vivo derived embryos - Sasithorn Panasophonkul (2018)
The study was conducted to examine the effect of different parthenogenetic activation (PA) protocols on developmental competence and quality of embryos, and to establish the parthenogenetic embryonic stem (ptES)-like cells in pigs. Compacted cumulus-oocyte complexes (COCs) were collected from porcine ovaries and then cultured in M199-medium. After 44 hrs of culture, matured MII-oocytes were selected and divided into three groups. Oocytes in each group were stimulated with three different activation protocols as protocol I: 1.36 kV/cm, 30 μsec, 2 pulses; protocol II: 1.50 kV/cm, 60 μsec, 2 pulses and protocol III: 1.0 kV/cm, 80 μsec, 3 pulses, and followed by exposure to 6-dimethylaminopurine (6-DMAP) for 4 hrs. The development to blastocyst stage at day 7 was significantly greater in protocol III-activated oocytes (31.88%) than in protocol I- and II-activated oocytes (2.83% and 25.88%, respectively; p<0.05), however, no significant difference in the mean number of blastocyst cells among the groups. Subsequently, whole ZP-free blastocysts produced from protocol III were cultured on STO feeder layers to evaluate the establishment of ES cells by comparing them with those produced in vivo. No forming of primary ES-like colonies was found in PA group comparing with in vivo group (0% and 25%, respectively; p<0.05). The primary colonies derived from in vivo blastocysts showed typical morphology of ES cells, meanwhile revealed positive AP activity. In conclusion, our study indicates that pig ES-like cells can be established from in vivo produced blastocysts and their blastocysts formation was optimal when three 80-msec consecutive pulses of 1.0 kV/cm was used, however, the high quality of blastocysts in term of the number of ICMs is a crucial criterion to lead the success of ptES-like cells establishments.